An introduction to Majorization‐Minimization algorithms for machine learning and statistical estimation - Nguyen, Hien D. (Wiley interdisciplinary reviews. Data mining and knowledge discovery, 2017)
MM (majorization–minimization) algorithms are an increasingly popular tool for solving optimization problems in machine learning and statistical estimation. This article introduces the MM algorithm framework in general and via three commonly considered example applications: Gaussian mixture regressions, multinomial logistic regressions, and support vector machines. Specific algorithms for these three examples are derived and Mathematical Programming Series A numerical demonstrations are presented. Theoretical and practical aspects of MM algorithm design are discussed. WIREs Data Mining Knowl Discov 2017, 7:e1198. doi: 10.1002/widm.1198 This article is categorized under: Algorithmic Development > Statistics Technologies > Machine Learning Technologies > Statistical Fundamentals A quadratic majorizer for the absolute value function.